Konvergensi Penurunan Stunting Berbasis KUA di Provinsi Lampung - Kirana, Fidelia (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
The Ministry of Religious Affairs (MORA) of the Republic of Indonesia fully supports the national program to accelerate stunting reduction. Efforts can be made by optimizing the role of the Office of Religious Affairs (KUA) in facilitating the Ministry of Health and BKKBN related to stunting prevention materials at the marriage guidance session of brides-to-be. Extension workers and facilitators of marriage guidance take a strategic role with community service related to how Religion is present in efforts to prevent and reduce stunting. This study collected some irregularities obtained from some relevant research results then organize the data for new sources of information. The collecting data, it was carried out by interviewing several informants, such as, Head of the Sakinah Family Sub-Directorate of MORA of the Republic of Indonesia, Bappeda of Lampung Province, Field of Islamic Religious Affairs of the Provincial Regional Office, and Section of the Islamic Bimas Office of MORA of the City Regency. The results of this study that the Ministry of Religion through KUA has a very important role, namely regionally providing, (1) Guidance for School-Age Adolescents as an introduction to themselves and the environment, (2) Guidance for Premarital Age Adolescents provides assistance/guidance about the concept of Qurani Adolescents, (3) Marriage Guidance that provides understanding/guidance to prospective brides in family preparation, (4) Sakinah Heritage to increases understanding to prospective parents with a religious approach and local wisdom, as well as preparing a quality generation.